Who wants to be an entrepreneur? : understanding the lack of local entrepreneurship in Singapore through a sociological lens. - Low, Raymond Wee Guan. (2010)
This project explores the subject of entrepreneurship through a sociological lens; it seeks to identify the socio-political and cultural obstacles interplay that may have potentially stifled the growth of local entrepreneurship and contributed to the paucity of local entrepreneurs in Singapore. Despite the many government initiatives to promote entrepreneurship, coupled with experts’ view of Singapore as an excellent place for doing business due to its political stability, why is there still a dearth of local entrepreneurs in Singapore? The research findings suggest that the answer lies in the socio-political climate and cultural norms and values that exist in the Singapore society. This research aims to fill the void in entrepreneurship studies in Singapore through a sociological inquiry by focusing on social, political, and cultural factors, instead of the conventional economic ones, that could be used to explain for the phenomenon.